Application of Used Tyres and Waste Building Materials in The Design Concept of Breakwater Structures - Muhammad Irsyaduddin Bin Mohd Zafaruddin; Mohd Idrus Bin Mohd Masirin (Recent Trends in Civil Engineering and Built Environment, 2021)
Coastal erosion occurs in almost many national coastlines in the world. This incident may be due to climate change being experienced around the world. Global warming and rising sea levels are also likely to contribute to this phenomenon. In this study, a comparison between several types of breakwater structure designs that have been identified is used for the purpose of producing a conceptual design of breakwater structures. This design is done using used tires and discarded building materials. An analysis of the effectiveness of the design concept of the breakwater structure can be produced through a comparison of the features that have been identified from the literature review. As a result of this study, the researchers found that the design concept called MyBREAKER which works like the construction concept of breakwater structures compared to existing breakwater structures and can contribute to a more economical construction. A comparison of breakwater structure design concept found, there are advantages on MyBREAKER as a breakwater structure and it not only contributes to reducing its construction cost but also more environmentally friendly and reduces pollution to the environment by reusing used and waste materials. The advantage of MYBREAKER is that it can shorten construction time while reducing labor and equipment costs because the time taken is shorter at the same time it can reduce the effects of corrosion on the breakwater structure itself and absorb waves more effectively than existing breakwater structures. However, an in -laboratory test on a small model needs to be performed to confirm the results of this study as suggested at the end of this report.